Contribution of the TNF-α (Tumor Necrosis Factor-α)–TNF-Rp55 (Tumor Necrosis Factor Receptor p55) Axis in the Resolution of Venous Thrombus. Issue 11 (November 2018) - Nosaka, Mizuho; Ishida, Yuko; Kimura, Akihiko; Kuninaka, Yumi; Taruya, Akira; Furuta, Machi; Mukaida, Naofumi; Kondo, Toshikazu
Abstract : Objective—: Deep vein thrombosis results from a combination of risk factors including genetic conditions, obesity, drugs, pregnancy, aging, and malignancy. We examined pathophysiological roles of the TNF-α (tumor necrosis factor-α)–TNF-Rp55 (tumor necrosis factor receptor p55) axis in thrombus resolution using Tnfrp5 5 −/− (TNF-Rp55–deficient) mice. Approach and Results—: On ligating the inferior vena cava of wild-type (WT) mice, venous thrombi formed and grew progressively until 5 days but shrunk to <50% of the thrombus weight at day 14. Concomitantly, inferior vena cava ligation enhanced intrathrombotic gene expression of Tnfa and Tnfrp55, and intrathrombotic macrophages expressed both TNF-α and TNF-Rp55 proteins. In Tnfrp5 5 −/− mice treated with the same manner, thrombus formed at a similar rate for 5 days, but shrinking was delayed compared with WT mice. Moreover, the blood flow recovery in thrombosed inferior vena cava was suspended in Tnfrp5 5 −/− mice compared with WT mice. Intrathrombotic Plau (urokinase-type plasminogen activator), Mmp2 (matrix metalloproteinase 2), and Mmp9 (matrix metalloproteinase 9) mRNA expression was significantly reduced in Tnfrp5 5 −/− mice, compared with WT ones. Supportingly, the administration of anti–TNF-α antibody or TNF-α inhibitor (etanercept) delayed the thrombus resolution in WT mice. Furthermore, TNF-α treatment enhanced gene expression of Plau, Mmp2, and Mmp9 in WT macrophages but not Tnfrp5 5 −/− macrophages. These effects were significantly suppressed by ERK (extracellular signal regulated kinase) and NF-κB (nuclear factor-kappa B) inhibitors. Therefore, the lack of TNF-Rp55 has detrimental roles in the thrombus resolution by suppressing PLAU, MMP-2, and MMP-9 expression. In contrast, TNF-α administration accelerated thrombus resolution in WT but not Tnfrp5 5 −/− mice. Conclusions—: The TNF-α–TNF-Rp55 axis may have essential roles in the resolution of venous thrombus in mice. Abstract : Supplemental Digital Content is available in the text.